(untitled) (Research, Society and Development, 2024)
The present work is a scoping review protocol on the role of the intestinal microbiota in the development of depression. Its objective was to identify the relationship between the intestinal microbiota and dysbiosis caused by depression. It was based on the methodology of the Joanna Briggs Institute (JBI), and was guided by the review question in terms of the conceptual model: Population, Concept and Context - PCC. The study will be carried out according to the Lilacs, Google Scholar and Pubmed databases. The author will develop a table in the GoogleDocs software for extracting and organizing data. Data identification will be carried out in the Rayyan® software by two groups of independent reviewers and a reviewer. The results will be displayed in a flow diagram, emphasizing the research process and including: identification, screening, eligibility and inclusion of the studied literature.